PEMANFAATAN LEARNING MANAGEMENT SYSTEM (LMS) DALAM PENGELOLAAN PEMBELAJARAN DARING PADA SATUAN PENDIDIKAN - I GUSTI NGURAH WIRAGUNAWAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The composition of the article on Utilization of Learning Management Systems (LMS) in Online Learning Management means to decide the adequacy of involving LMS in further developing understudy learning results during web based learning. The composition of this article is a writing concentrate on movement, to be specific by looking at different wellsprings of articles connected with the issues and destinations of the examination. The necessary information were gathered through printed investigations and afterward dissected utilizing content examination procedures. The utilization of LMS in learning makes it more straightforward for instructive foundations to further develop the learning system, gaining can be gotten to from different spots and limitless times, and learning can be completed all the more just. The utilization of LMS likewise makes learning more adaptable as far as study time and makes understudies more autonomous. Instructors can likewise screen understudy exercises through the LMS exhaustively. The outcomes got in light of the writing inspected include: (1) LMS is a media that is in extraordinary interest in web based realizing which is described by a significant degree of trust of 82.2% (2) LMS enjoys the benefit of complete elements contrasted with other internet based media so that learning happens more changed (3) Learning utilizing LMS or a mix of LMS-based learning models has been demonstrated to build the action, learning results, and inspiration of understudies in the